2008
DOI: 10.1007/s00423-008-0320-8
|View full text |Cite
|
Sign up to set email alerts
|

The recurrent laryngeal nerve and the inferior thyroid artery—anatomical variations during surgery

Abstract: To avoid the risk of nerve damage during thyroid surgery, a good knowledge of the variations of the inferior laryngeal nerve is essential. This is important to achieve an undisturbed quality of life for the thyroid patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
59
3
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 27 publications
3
59
3
2
Order By: Relevance
“…Our study showed 4 (80%) of the bifurcated nerves to be in the left sided and 1 on the right side. Similar results were seen in the study by Makay et al 11 where bifurcation of the nerve was mostly observed on the left side. However Casella et al 13 found 36 of 195 (18.5%) nerves showing extra-laryngeal branching of which 27 (25.5%) were right and 9 left sided (p = 0.0088).…”
Section: Discussionsupporting
confidence: 91%
“…Our study showed 4 (80%) of the bifurcated nerves to be in the left sided and 1 on the right side. Similar results were seen in the study by Makay et al 11 where bifurcation of the nerve was mostly observed on the left side. However Casella et al 13 found 36 of 195 (18.5%) nerves showing extra-laryngeal branching of which 27 (25.5%) were right and 9 left sided (p = 0.0088).…”
Section: Discussionsupporting
confidence: 91%
“…Thyroid surgery requires a thorough knowledge of the RLN and its anatomical variations. This is of utmost importance, since it is well known that variations of the RLN are prone to iatrogenic injuries [12]. Giving more researches on these variations is essential to prevent damage to the nerve.…”
Section: Discussionmentioning
confidence: 99%
“…However, recurrent laryngeal nerves with abnormal anatomy are still susceptible to injury. Based on the literature, several variations of recurrent laryngeal nerves have been reported [1][2][3][4][5]. Similar to the non-recurrent laryngeal nerve, the variants identified in this study were all located on the right side, but not directly divided from the vagus, and divided into intracranial branches except for the tracheal, esophageal, and laryngeal branches.…”
Section: Discussionmentioning
confidence: 80%
“…Therefore, the clarification and recognition of the variation and passage of recurrent laryngeal nerves are very important for preventing postoperative complications. To date, multiple variations of the recurrent laryngeal nerve have been reported [1][2][3][4][5]. Here, we reported a new variation of the right recurrent laryngeal nerve that should be carefully considered during neck surgery.…”
mentioning
confidence: 93%